Making embedded software reuse practical and safe. - Leveson, Nancy G. (Software engineering notes.)
Reuse of application software has been limited and sometimes has led to accidents. This paper suggests some requirements for successful and safe application software reuse and demonstrates them using a case study on a real spacecraft.